2011
DOI: 10.1021/jo101942f
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Diimine: A Highly Selective Catalyst System for the Base-Free Oxidative Heck Reaction

Abstract: Pd(OAc)(2)/3 is an efficient catalyst system for the base-free oxidative Heck reaction that outperforms the currently available catalysts for the more challenging substrates studied. The catalyst system is highly selective, and works at room temperature with dioxygen as the oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.63–7.56 (d, J = 16.1 Hz, 1H), 7.55–7.49 (m, 2H), 7.42–7.34 (m, 3H), 6.41–6.35 (d, J = 16.1 Hz, 1H), 1.55 (s, 9H). 39 …”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.63–7.56 (d, J = 16.1 Hz, 1H), 7.55–7.49 (m, 2H), 7.42–7.34 (m, 3H), 6.41–6.35 (d, J = 16.1 Hz, 1H), 1.55 (s, 9H). 39 …”
Section: Methodsmentioning
confidence: 99%
“…(8) Some recent developments involve oxygen and base-free reactions without external oxidant(9) and the identification of new nonphenanthroline type ligands. (10)…”
Section: Introductionmentioning
confidence: 99%
“…The use of acrolein in an oxidative Heck is limited,(18) but the palladium(II)-catalyzed Heck coupling of the related methyl vinyl ketone with various boronic acids has been reported with yields between 50% and 88%. 4,8,10,31 …”
Section: Introductionmentioning
confidence: 99%
“…Although many previous studies focused on oxidative Heck reactions of activated alkenes such as cyclohexenones[16] and acrylate esters,[15] several recent studies have reported high yields and in several cases excellent regioselectivities in oxidative Heck reactions of isolated alkenes. [1719] This sets the stage for development of this reaction into a protein ligation strategy for isolated alkene systems.…”
mentioning
confidence: 99%
“…We had developed BIAN earlier as a superior ligand for oxidative Heck reactions of challenging substrates. [16] Using mass spectrometry we demonstrated selective and complete ligation of a fluorescently labeled phenylboronic acid derivative to protein-bound alkenes, even in the presence of complex protein mixtures from cell lysates.…”
mentioning
confidence: 99%